2019
DOI: 10.1519/jsc.0000000000003439
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Determinants of the Modified and Traditional 505 Change of Direction Speed Test

Abstract: The aim of this study was to investigate the whole-body biomechanical determinants of 180° change of direction (COD) performance. 61 male athletes (age: 20.7 ± 3.8 years, height: 1.77 ± 0.06 m, mass: 74.7 ± 10.0 kg) from multiple sports (soccer, rugby, and cricket) completed 6 trials of the modified and traditional 505 on their right leg, whereby 3D motion and ground reaction force data were collected during the COD. Pearson's and Spearman's correlations were used to explore the relationships between biomechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
146
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(157 citation statements)
references
References 39 publications
11
146
0
Order By: Relevance
“…Likewise, in relation to linear velocity, the application of forces in the horizontal vector during sprint determined by the variable RF-10M showed high correlation with COD90°. In line with this, other studies [ 14 , 57 ] have found that those team sports’ athletes who performed better in the COD 505 test showed higher maximum horizontal propulsion forces and shorter ground contact times, as well as equally higher approaching velocities and greater speed reductions during cutting action. The key to better performance in COD actions is to minimize contact times in the field [ 14 ], and strength affords the ability to do so.…”
Section: Discussionsupporting
confidence: 72%
“…Likewise, in relation to linear velocity, the application of forces in the horizontal vector during sprint determined by the variable RF-10M showed high correlation with COD90°. In line with this, other studies [ 14 , 57 ] have found that those team sports’ athletes who performed better in the COD 505 test showed higher maximum horizontal propulsion forces and shorter ground contact times, as well as equally higher approaching velocities and greater speed reductions during cutting action. The key to better performance in COD actions is to minimize contact times in the field [ 14 ], and strength affords the ability to do so.…”
Section: Discussionsupporting
confidence: 72%
“…Consequently, the opposite leg was ascertained to be the leg used to jump off when performing a right-handed running basketball layup and was identified as the stance leg (SL) [ 29 ]. Participants were divided into faster (top 33%, n = 13) and slower (bottom 33%, n = 13) performers based on their completion time [ 17 ] to test the hypothesis of the effect of COD performance. In addition, participants were divided into a high-playing-level group ( n = 17), engaged in basketball training and competitions at collegiate and national levels (>3 training sessions per week; >5 years of basketball experience), and a low-playing-level group ( n = 23), engaged in basketball as a recreational activity (<3 sessions per week), to test the hypothesis of the effect of playing level.…”
Section: Methodsmentioning
confidence: 99%
“…Focusing solely on the 180° COD speed tests, the kinetic and kinematic variables of the penultimate foot contact (PFC) and final foot contact (FFC) are commonly evaluated during traditional and modified 505 tests to investigate the differences between faster and slower performers [ 15 , 16 , 17 ]. Recently, new research investigated for the first time the antepenultimate foot contact, demonstrating its role in facilitating the deceleration phase during a traditional 505 test [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Dos'Santos and colleagues [38] observed improvements in COD performance and movement quality following a six-week training intervention centred around improving technical components of COD. Considering the high level of physical and technical demands elicited during COD and agility actions [16,39], greater variance in test performance may be observed in younger, more immature athletes, particularly during periods of rapid growth and development.…”
Section: Introductionmentioning
confidence: 99%